THE HEROIC BATTLE OF MOUNT MUSA AND THE VALIANT DEEDS OF THE ARMENIAN WOMEN - Minasyan, Edik (Armenian Folia Anglistika, 2024)
This article, dedicated to the 90th anniversary of Franz Werfel’s heroic novel The Forty Days of Musa Dagh, presents the valiant deeds and heroism of Armenian women during the self-defense of Mount Musa, when Mount Musa of Suetia province became one of the prominent self-defense centers of Armenians. Our analysis of this heroic episode of Armenian history presents the reader with a new genocidal policy adopted and elaborated against the Armenians by the government of the Ottoman Empire in 1915. In our study, we have used works published in Armenia and abroad, some of which are primary sources.